For the love of risk ? When Local Inhabitants’ and Outsiders’ Imaginaries Match: The Case of the Verbier Resort in the Swiss Alps - Cretton, Viviane; Decorzant , Yann (Quaderns de l’Institut Català d’Antropologia, 2023)
This article focuses on a mountain region in the Swiss Alps that has built an international name for itself since the 1960s upon a specific ski resort, Verbier. From the very beginning, the locals involved in the development of the place were risk-takers, revealing an entrepreneurial spirit that lasts up until now. Over time, the mountain resort has attracted outsiders who share a taste for risk-taking, not only in the field of sport but also in the worlds of finance, art or business. Some emblematic Verbier projects chosen for this article (Xtreme, E-Bike Festival, Art Summit, Mountain Hub) perfectly embody the concordance of interests between locals and non-locals when it comes to exploiting the mountain capital of the place. While highlighting the wider socio-economic and political context in which it is embedded, the paper emphasizes how the whole process of promoting Verbier internationally as a global playground for risk taking, through various win-win corporate strategies negotiated between locals and outsiders, might provide a kind of “vernacular cosmopolitanism”, or “rooted cosmopolitanism”. Beyond the specificity of the case study, it explores how global and local forces interact and intertwin to affect mountain locations and reshape the imaginaries and values of locality.